1991
DOI: 10.1080/00480169.1991.35681
|View full text |Cite
|
Sign up to set email alerts
|

IgA multiple myeloma in a dog

Abstract: Multiple myeloma was diagnosed in a lo-year-old female Labrador which showed signs of weight loss, lethargy and skeletal pain. Radiography revealed well circumscribed osteolytic lesions in vertebrae, sternebrae, and the left humerus and radius along with generalised osteoporosis. The number of plasma cells in the bone marrow was increased and the serum gamma globulin concentration was elevated. Treatment with cyclophosphamide, mephalan and prednisone successfully controlled the malignancy but also resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…Serum hyperviscosity and its associated syndrome (i.e., hypertension, eye damage, kidney disease, and bleeding) are attributable to the presence of an IgA type MC (Hendrix et al 1998;Matus et al 1986). The remission of symptoms after melphalan administration is in agreement with data reported by Cayzer and Jones (1991), Hendrix et al (1998), andMatus et al (1986). Cayzer and Jones (1991) also reported that the average survival time of patients treated with prednisone alone or in combination with melphalan is 220 and 540 days, respectively, and that there is a significant correlation between survival time and response to therapy.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Serum hyperviscosity and its associated syndrome (i.e., hypertension, eye damage, kidney disease, and bleeding) are attributable to the presence of an IgA type MC (Hendrix et al 1998;Matus et al 1986). The remission of symptoms after melphalan administration is in agreement with data reported by Cayzer and Jones (1991), Hendrix et al (1998), andMatus et al (1986). Cayzer and Jones (1991) also reported that the average survival time of patients treated with prednisone alone or in combination with melphalan is 220 and 540 days, respectively, and that there is a significant correlation between survival time and response to therapy.…”
Section: Discussionsupporting
confidence: 92%
“…The remission of symptoms after melphalan administration is in agreement with data reported by Cayzer and Jones (1991), Hendrix et al (1998), andMatus et al (1986). Cayzer and Jones (1991) also reported that the average survival time of patients treated with prednisone alone or in combination with melphalan is 220 and 540 days, respectively, and that there is a significant correlation between survival time and response to therapy. It has also been reported that 90% of subjects treated with prednisone combined with melphalan respond positively and that survival time is not influenced by either continuous or intermittent (during periods of burning or disease relapse) treatment (Cayzer and Jones 1991;Hendrix et al 1998;Mayer et al 2008 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations